PERAN RISIKO PAJAK DALAM MEMODERASI PENGARUH PENGHINDARAN PAJAK TERHADAP RISIKO PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Annisa Dwi Amalia P; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This research aims to examine the effect of tax avoidance on firm risk. In addition, this study investigates whether tax risk acts as a moderating variable in the relationship between tax avoidance and firm risk. This research adopts a quantitative approach using multiple linear regression to test the hypotheses. Tax avoidance is measured using the Effective Tax Rate (ETR) as a proxy, tax risk is proxied by the volatility of ETR, and firm risk is measured by the volatility of stock returns. The research sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. The final sample analyzed includes 321 observations from 111 companies. Data processing and regression analysis were conducted using the EViews 13 application.The results indicate that tax avoidance has no significant effect on firm risk. However, tax risk has a positive and significant effect on firm risk. Furthermore, the analysis shows that tax risk does not moderate the relationship between tax avoidance and firm risk. Therefore, tax risk is more appropriately analyzed independently rather than as a moderating factor when assessing the impact of tax avoidance on firm risk.